Phosphodiesterase Type 5 Inhibitors in Male Reproduction: Molecular Mechanisms and Clinical Implications for Fertility Management - Aris Kaltsas; Fotios Dimitriadis; Athanasios Zachariou; Nikolaos Sofikitis; Michael Chrisofos (Cells)
Phosphodiesterases, particularly the type 5 isoform (PDE5), have gained recognition as pivotal regulators of male reproductive physiology, exerting significant influence on testicular function, sperm maturation, and overall fertility potential. Over the past several decades, investigations have expanded beyond the original therapeutic intent of PDE5 inhibitors for erectile dysfunction, exploring their broader reproductive implications. This narrative review integrates current evidence from in vitro studies, animal models, and clinical research to clarify the roles of PDEs in effecting the male reproductive tract, with an emphasis on the mechanistic pathways underlying cyclic nucleotide signaling, the cellular specificity of PDE isoform expression, and the effects of PDE5 inhibitors on Leydig and Sertoli cell functions. Although certain findings suggest potential improvements in sperm motility, semen parameters, and a more favorable biochemical milieu for spermatogenesis, inconsistencies in study design, limited sample sizes, and inadequate long-term data temper definitive conclusions. Addressing these gaps through standardized protocols, larger and more diverse patient cohorts, and explorations of mechanistic biomarkers could pave the way for incorporating PDE5 inhibitors into evidence-based fertility treatment strategies. In the future, such targeted approaches may inform individualized regimens, optimize male reproductive outcomes, and refine the clinical application of PDE5 inhibitors as part of comprehensive male fertility management.